STRENGTHENING THE CAPACITY OF POSYANDU (INTEGRATED HEALTH SERVICE POST) CADRES IN UTILIZING THE PANDUREJO APPLICATION FOR DIGITAL-BASED HEALTH DATA AND INFORMATION MANAGEMENT - Rokhayati -; Este Latifahanun (Jurnal Pengabdian Kepada Masyarakat Mulia Madani Yogyakarta, 2026)
The utilization of information technology has become an urgent necessity across various aspects of public service, including the health sector. One application of this technology is the "Pandurejo Application," a digital recording system designed to enhance Integrated Health Services Post and improve the data management capabilities of health cadres. Integrated Health Services Post programs play a vital role, enabling the community to access information regarding maternal and child health. As the frontline of community health services, Integrated Health Services Post cadres are crucial to the processes of collecting, recording, managing, and reporting health data. However, some volunteers still face limitations regarding the use of digital applications, electronic data management, and the utilization of health information to Integrated Health Services Post. Optimizing the use of the application required capacity-building support for the cadres, which was provided through a community service activity held on Thursday, June 11, 2026, in Demangrejo Village, Kulon Progo Regency. The implementation method comprised several stages: preparation, education on the Pandurejo application, a usage demonstration, hands-on practice with mentoring, and monitoring and evaluation. Overall, this community service activity successfully strengthened the capacity of Integrated Health Services Post cadres to utilize the Pandurejo Application for digital-based health data and information management.